Bearing witness : a resource guide to literature, poetry, art, music, and videos by Holocaust victims and survivors - Rosen, Philip, 1928- (Greenwood Press, 2002)
"This resource guide will help readers locate over 800 first-person accounts, fiction, poetry, art interpretations, and music by Holocaust victims and survivors, as well as videos relating the testimony and experiences of Holocaust survivors. In addition to the few well-known writers, artists, and musicians whose work so eloquently captures their experience during the Holocaust, this guide introduces the work of more than 250 lesser known or unrecognized writers, artists, and musicians from many countries who documented their experience of persecution at the hands of the Nazis. This guide will help students to gain firsthand knowledge of what it was like to experience the Holocaust and how ordinary people created art and meaning from the ashes of their lives."--Jacket